Variabel Anteseden Organizational Citizenship Behavior (OCB) dan Pengaruhnya terhadap Service Quality pada Perguruan Tinggi Swasta di Surabaya - Djati, S. Pantja (Jurnal Aplikasi Manajemen, 2009)
The purposes of this research are to analyze the influence of employee morality, commitment, and motivation towards organizational citizenship behavior and its influence towards the quality of service. The population of this research is divided into two parts, namely all administrative employees of private universities in Surabaya which have students over 5000 and students who are being serviced of had been serviced directly by the administrative employees. The sample chose for this research are 133 employees and 133 university students by using the proportional non-random sampling. Structural equation modeling is used as the analysis technique with a five-percent significance level. The research findings revealed that the quality of services for student, which are delivered by the administration staffs of private universities in Surabaya, is good. The organization citizenship behavior of employees, moral, commitment, and motivation of administrative staffs in private universities in Surabaya are good enough. According to the result of SEM testing revealed that the moral, commitment, and motivation of employees have significant influence towards organizational citizenship behavior which later also influence the service quality. This research also found out that moral, commitment, and motivation are the antecedent variables of employee's organizational citizenship behavior. Moreover, to be able to give good service, employees should develop the organizational citizenship behavior.